The Effectiveness of Coriander Seed Extract (Coriandrum Sativum) on Lowering Cholesterol Levels in Elderly Patients with Hypercholesterolemia - Setyowati, Ana; Ulya, Ni’matul (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
The World Health Organization (WHO) estimates that by 2025 the number of elderly people worldwide will reach 1.2 billion people which will continue to grow up to 2 billion people in 2050. Cholesterol is important for our body, but in fact excessive cholesterol levels in the blood can be harmful to health since that can cause hypertension and blockage of the blood vessels of the brain, heart and leg. Actually, Hypercholesterolemia in the elderly can be reduced by non-pharmacological treatment using coriander seeds. The purpose of this study was to determine how much decreased cholesterol levels in elderly patients with hypercholesterolemia. This research is a quasi-experimental study with coriander seed extract as a treatment. The sampling is using multistage random sampling technique of 15 elderly people per group. The data analysis technique used an independent T test. The results showed that the significance value of the treatment group and the control group before was 0.063, while the significance value after treatment was 0.038. This research can contribute to the community and health workers to seek herbal treatment methode for the elderly with hypercholesterolemia.